HEALTH ANXIETY AMONG GENERAL MEDICAL OUT PATIENTS OF PUBLIC AND PRIVATE SECTOR HOSPITALS IN FAISALABAD - Dr. Riffat Sadiq; Abrish Ali Khan; Fatima Jameel (International Journal of Contemporary Issues in Social Sciences, 2024)
The present study investigated health anxiety among patients of general outpatient departments of public and private sector hospitals in Faisalabad. In order to meet that research objective, Health Anxiety Questionnaire (HAQ), developed by Lucock and Morely (1996), was translated and adapted in Urdu language to extend its application for the population whose first language is Urdu. Reliability and validity analysis proved Urdu version of HAQ as standardized tool for examining health anxiety. In the second phase, prevalence and gender difference was determined on the sample of one hundred and seventy six (n =176) patients selected from general outpatient departments. Ages of them ranged from 21 to 60 with mean age (M = 44.93; SD = 8.44). Data were collected via demographic information sheet and Health Anxiety Questionnaire (HAQ). Statistical analysis revealed majority of patients experiencing moderate level of health anxiety, while women reported more health anxiety pertaining to their current physical health status as compared to men in terms of health worry and preoccupation, fear of illness and death, re-assurance seeking behavior and interference with life. Present findings imply the integration of psychological assessment and treatment procedures while dealing patients suffering from physical complaints.